POTRET PEREMPUAN JAWA DI JORONG MAHAKARYA, KENAGARIAN KOTO BARU, PASAMAN (STUDI KASUS PEDAGANG SAYUR KELILING TAHUN 1995-2010). - Juwita, Rahma - (Pendidikan Sejarah, 2014)
This thesis discusses about social economic life of women as vegatables trader arounded at Jorong Mahakarya, Kenagarian Koto Baru. It study about the beginning and social economic form before and after they become a vegetables trader around. For make this research be easy , so it can be formulated of problems, as follow : 1) How The women as vegetables trader arounded at Jorong Mahakarya, Kenagarian Koto Baru.2) How the social economic life of vegetables trader arounded . The pupose of this research are 1) To decribe the arrival of the women as vegetables trader barounded at Jorong Mahakarya , Kenagarian Koto Baru,2) To describe life social economic of vegetables trader aroundedÂ  at Jorong Mahakarya , Kenagarian Koto Baru before and after be a vegetables trader arounded .The method be used in this writing is history method , that consist of four stages, they are : heuristic, critic sources, interpretaion and historiogrpahy.